Characterizing Indicators of Students' Productive Disciplinary Engagement - Swenson, Jessica E.; Wendell, K. (Tufts Archival Research Center, 2017)
Engineering science courses are typically taught with lecture-based pedagogies and routinely assign problems sets comprised of problems authored by the professor or from the course textbook. With the high number of required engineering science courses, students spend a substantial amount of out-of-class effort on these types of problems. Yet, there is little research on how students engage in and learn from these problem sets.This study examines three groups of students while they work on fluid mechanics problem sets and identifies instances and origins of productive disciplinary engagement. When students disagreed and debated how to solve problems, they engaged in productive disciplinary discussion. Three factors contributed to this active discussion and disciplinary engagement: the nature of the problem, the norms of the class, and the goals of the students. Our findings have implications for designing problem types that include conflicting constraints or require students to debate for a worked out solution.